(untitled) (Mustansiria Dental Journal, 2018)
The aim of this study was to compare the effect of two professional bleaching products (in-office Opalescence Boost hydrogen peroxide 38%) and (home bleaching Opalescence carbamide peroxide 35%) on enamel microhardness. The sample consist of thirty maxillary first premolars teeth (freshly extracted), caries free obtained from children aged 12 years old under routine orthodontic treatment. The teeth were sectioned mesiodistally parallel to the long axis of tooth and mounted on acrylic mold. The specimens were divided into two halves buccal and palatal as per treatment, the buccal half served as experimental, while the palatal half served as control (1) and kept in artificial saliva at 37c0 for two weeks. Microhardness test were obtained before and after bleaching. Results indicated that teeth specimens submitted to Opalescence carbamide peroxide 35% showed highly significant reduction in enamel microhardness P<0.01, while no-significant difference in enamel microhardness in specimens submitted to Opalescence Boost 38% hydrogen peroxide P>0.05. In this study Opalescence carbamide peroxide 35% leads to the significant decrease in enamel microhardness compared to Opalescence Boost hydrogen peroxide 38%.